2020
DOI: 10.1200/jco.20.01336
|View full text |Cite|
|
Sign up to set email alerts
|

Prospective Cohort Study of Pre- and Postdiagnosis Physical Activity and Endometrial Cancer Survival

Abstract: PURPOSE The aim of this study was to evaluate associations between pre- and postdiagnosis physical activity and survival in survivors of endometrial cancer by physical activity domain, intensity, dose (metabolic-equivalent task [MET]-hours/week/year), and change from pre- to postdiagnosis. METHODS We conducted a prospective cohort study in Alberta, Canada, of 425 women who were diagnosed with histologically confirmed invasive endometrial cancer between 2002 and 2006 and observed to 2019. The interviewer-admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Accumulating large prospective and epidemiologic studies have suggested that highlevels of physical activity against obesity can reduce the risk of endometrial cancer, whereas sedentary behavior can increase such risk [32][33][34]. Furthermore, recently, a prospective study by Friedenreich et al [35] has observed that increased physical activity after a diagnosis of endometrial cancer is associated with better survival and suggested that health care professionals should recommend physical activity as a therapeutic intervention to patients with newly diagnosed endometrial cancer and endometrial cancer survivors to improve their survival outcomes. Given that inflamed VAT can be regarded as a causal mechanism of obesity-induced endometrial cancer, it is conceivable that V/S ratio evaluated by 18 F-FDG PET/CT could be useful for assessing responses to therapeutic interventions for obesity such as exercise or lifestyle modification in patients with endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating large prospective and epidemiologic studies have suggested that highlevels of physical activity against obesity can reduce the risk of endometrial cancer, whereas sedentary behavior can increase such risk [32][33][34]. Furthermore, recently, a prospective study by Friedenreich et al [35] has observed that increased physical activity after a diagnosis of endometrial cancer is associated with better survival and suggested that health care professionals should recommend physical activity as a therapeutic intervention to patients with newly diagnosed endometrial cancer and endometrial cancer survivors to improve their survival outcomes. Given that inflamed VAT can be regarded as a causal mechanism of obesity-induced endometrial cancer, it is conceivable that V/S ratio evaluated by 18 F-FDG PET/CT could be useful for assessing responses to therapeutic interventions for obesity such as exercise or lifestyle modification in patients with endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that active physical activity is associated with improved survival after an endometrial cancer diagnosis in a prospective cohort study by Friedenreich et al [ 71 ]. 425 women with endometrial cancer were followed up for a median of 14.5 years and the interviewer-administered Lifetime Total Physical Activity Questionnaire recorded pre- and post-diagnosis physical activity.…”
Section: Uterine Corpusmentioning
confidence: 99%
“…Despite guidelines for nutrition and exercise for people with cancer 7 , 8 and well-established benefits of pre and post-diagnosis physical activity (PA) including improvements in cardiovascular health, health-related quality of life (HRQoL), 9 , 10 fatigue, 11 and survival, 12 , 13 ; few endometrial cancer patients meet the recommendations (27% nutrition and 12% exercise). 4 , 14 Endometrial cancer survivors report that specific PA and nutrition recommendations were rarely made by oncologists.…”
Section: Introductionmentioning
confidence: 99%